2014
DOI: 10.1016/j.abb.2014.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Na,K-ATPase reconstituted in ternary liposome: The presence of cholesterol affects protein activity and thermal stability

Abstract: Differential scanning calorimetry (DSC) was applied to investigate the effect of cholesterol on the thermotropic properties of the lipid membrane (DPPC and DPPE). The thermostability and unfolding of solubilized and reconstituted Na,K-ATPase in DPPC:DPPE:cholesterol-liposomes was also studied to gain insight into the role of cholesterol in the Na,K-ATPase modulation of enzyme function and activity. The tertiary system (DPPC:DPPE:cholesterol) (molar ratio DPPC:DPPE equal 1:1) when cholesterol content was increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 42 publications
1
13
0
3
Order By: Relevance
“…This inhibition promoted by cholesterol is probably related to an increased membrane rigidity, which leads to phospholipid acyl chains "freezing" in the membrane. 42,45 In our study, we noticed that CAF showed a decrease in GSH content in the renal cortex ( Figure 4A) with a decrease in GSH levels and an increase in lipid peroxidation in the renal medulla ( Figure 4E,F, respectively). Among the parameters evaluated in the study by Noeman et al, 8 GSH content was significantly decreased in the renal tissue of the HFD group.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…This inhibition promoted by cholesterol is probably related to an increased membrane rigidity, which leads to phospholipid acyl chains "freezing" in the membrane. 42,45 In our study, we noticed that CAF showed a decrease in GSH content in the renal cortex ( Figure 4A) with a decrease in GSH levels and an increase in lipid peroxidation in the renal medulla ( Figure 4E,F, respectively). Among the parameters evaluated in the study by Noeman et al, 8 GSH content was significantly decreased in the renal tissue of the HFD group.…”
Section: Discussionmentioning
confidence: 51%
“…Another interesting result is shown in Figures C and F, where we demonstrate the relationship between phospholipids and cholesterol. It has been previously demonstrated that the addition of cholesterol to membrane mimetic systems may destabilize the phospholipid bilayer and alter protein conformation . Also, cholesterol concentration appears to have a direct effect on Na,K‐ATPase activity, with variations in its functioning due to its lack or excess in the membrane .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Proteoliposomes can be used to study how the protein-lipid interactions specifically affect the surface of the membrane model. The scientific community has highlighted this approach as an excellent tool to understand biochemical and biophysical phenomena and to evaluate biotechnological applications (Camolezi et al 2002;Ierardi et al 2002;Daghastanli et al 2004;De Lima Santos et al 2005;Rigos et al 2008;Santos et al 2009;Bolean et al 2010Bolean et al , 2011Bolean et al , 2015Simão et al 2010aSimão et al , 2010bBarbosa et al 2011;Yoneda et al 2013Yoneda et al , 2014Simão et al 2015;Dong et al 2016;Elkhodiry et al 2016). …”
Section: Liposomes and Nanobiotechnologymentioning
confidence: 99%